Analysis of initiatives to promote education for sustainability and climate action in schools in Madrid and proposals for improvement - Susana Sastre Merino; Cristine Zanarotti Prestes Rosa; Marvin Josué Izaguirres Betancourth (Revista Española de Pedagogía)
As a powerful tool for social change, education is one of the key transversal areas for promoting sustainability and addressing the climate emergency. This is reflected in international guidelines, such as the 2030 Agenda and the European GreenComp framework, and national guidelines, such as the current Spanish education law (LOMLOE). As a result, Spanish formal education has an opportunity to strengthen schools as strategic nodes for social change. However, there are several barriers that inhibit its true incorporation into the curriculum, such as teacher training and the lack of whole-school projects that address the topic, with many initiatives still being run on an occasional basis in isolation from the wider curriculum. To understand the external support available to schools for the integral incorporation of this approach, this study comprises a documentary analysis of the educational programs for sustainability and climate action offered by private, social, and public organisations in the city of Madrid. This analysis is complemented by a discussion group with relevant stakeholders from the ecosystem to assess the challenges and opportunities involved in promoting this approach. The results indicate that external organisations must adapt their offers to the new LOMLOE framework and support schools with training for teachers and management teams. They must also help schools implement programmes with a curricular and whole-school approach that is collaborative and contextualized. The entire educational community should be involved and the integration of these initiatives in public policies fostered.